Diagnostic laparoscopy in the evaluation of tubal factor in cases of infertility - Chaudhari, Arpana Dipakbhai; Baria, Anilkumar Mathurbhai; Chaudhari, Upendra Rameshbhai; Dixit, Grishma T.; Thakor, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Tubal factor infertility accounts for a large portion of female factor infertility. The most prevalent cause of tubal factor infertility is pelvic inflammatory disease and acute salpingitis. Tubal patency can be diagnosed by hysterosalpingography (HSG) or laparoscopy with chromopertubation. The aim of this study was to determine the role of laparoscopy in the evaluation of tubal factor in infertile women. Methods: Sixty women presenting with complaints of primary and secondary infertility were investigated for tubal disease by laparoscopy at at Smt. NHL Municipal Medical College, Ahmedabad during July 2011 to September 2013. Tubal patency was tested by chromopertubation using Methylene blue dye. Results: Thirty-five (58.3%) patients were in primary infertility group while 25 (41.7%) patients were in secondary infertility group. 80% women were in the age group of 21 to 30 years. In 49% of women, the duration of infertility was between 2 to 4 years whereas 17% cases had been infertile for 6 to 10 years. Diagnostic laparoscopy and findings of chromopertubation revealed unilateral blockage in 37% of cases, bilateral blockage had seen in 23% of cases, endometriosis was seen in 9% of cases and adhesion in 7% of cases. Conclusions: Unilateral and bilateral tubal blockade was detected in 60% of cases of infertile women.